Hypoxia as a physiological cue and pathological stress for coral larvae - Alderdice, Rachel; Pernice, Mathieu; Cárdenas, Anny; Hughes, David J.; Harrison, Peter L.; Boulotte, Nadine; Chartrand, Katie; Kühl, Michael; Suggett, David J.; Voolstra, Christian R. (Molecular ecology, 2022)
Ocean deoxygenation events are intensifying worldwide and can rapidly drive adult corals into a state of metabolic crisis and bleaching‐induced mortality, but whether coral larvae are subject to similar stress remains untested. We experimentally exposed apo‐symbiotic coral larvae of Acropora selago to deoxygenation stress with subsequent reoxygenation aligned to their night‐day light cycle, and followed their gene expression using RNA‐Seq. After 12 h of deoxygenation stress (~2 mg O2/L), coral planulae demonstrated a low expression of HIF‐targeted hypoxia response genes concomitant with a significantly high expression of PHD2 (a promoter of HIFα proteasomal degradation), similar to corresponding adult corals. Despite exhibiting a consistent swimming phenotype compared to control samples, the differential gene expression observed in planulae exposed to deoxygenation‐reoxygenation suggests a disruption of pathways involved in developmental regulation, mitochondrial activity, lipid metabolism, and O2‐sensitive epigenetic regulators. Importantly, we found that treated larvae exhibited a disruption in the expression of conserved HIF‐targeted developmental regulators, for example, Homeobox (HOX) genes, corroborating how changes in external oxygen levels can affect animal development. We discuss how the observed deoxygenation responses may be indicative of a possible acclimation response or alternatively may imply negative latent impacts for coral larval fitness.